2016
DOI: 10.1038/srep21199
|View full text |Cite
|
Sign up to set email alerts
|

High-Contrast Gratings based Spoof Surface Plasmons

Abstract: In this work, we explore the existence of spoof surface plasmons (SSPs) supported by deep-subwavelength high-contrast gratings (HCGs) on a perfect electric conductor plane. The dispersion relation of the HCGs-based SSPs is derived analyt- ically by combining multimode network theory with rigorous mode matching method, which has nearly the same form with and can be degenerated into that of the SSPs arising from deep-subwavelength metallic gratings (MGs). Numerical simula- tions validate the analytical dispersio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…In order to realize high-confinement SPPs at microwave and THz frequencies, corrugated metallic structures are proposed to support and propagate the SPPs, called spoof SPPs [11][12][13], which display very similar features in dispersion properties, subwavelength confinement, field enhancements, and environment sensitivity as those of the optical SPPs [14][15][16]. Much effort has been put into generating highly confined spoof SPPs with desired functions at microwave and THz frequencies [17][18][19][20][21][22]. Cui et al have demonstrated the guiding of spoof SPPs on ultrathin metal films to a very long distance at microwave frequencies [20].…”
Section: Introductionmentioning
confidence: 99%
“…In order to realize high-confinement SPPs at microwave and THz frequencies, corrugated metallic structures are proposed to support and propagate the SPPs, called spoof SPPs [11][12][13], which display very similar features in dispersion properties, subwavelength confinement, field enhancements, and environment sensitivity as those of the optical SPPs [14][15][16]. Much effort has been put into generating highly confined spoof SPPs with desired functions at microwave and THz frequencies [17][18][19][20][21][22]. Cui et al have demonstrated the guiding of spoof SPPs on ultrathin metal films to a very long distance at microwave frequencies [20].…”
Section: Introductionmentioning
confidence: 99%
“…The entries of the matrix M are of the form (8), where . The first (second) line in (8) is used for the lines of M coming from projections of the Ht continuity on the x (y) components of each mode.…”
mentioning
confidence: 99%
“…Since then, extensive theoretical and experimental works have been performed to verify the existence of spoof LSPs in various textured metallic structures [20][21][22][23][24]. In addition, we also have demonstrated that a hollow metallic cylinder corrugated by periodic cut-through slits can supports the magnetic and electric dipole resonances similar to the subwavelength dielectric nanoparticles with a high-refractive index at optical frequencies, as the spoof Mie resonant structure [25].…”
Section: Introductionmentioning
confidence: 97%